Solar system astrophysics. - Milone, E. F., 1939- (Astronomy and astrophysics library., 2008)
Covers solar system astrophysics, beginning with basic tools of spherical astronomy and celestial mechanics. This work also covers the Earth-Moon system and the interior planets; rocks and minerals, including crystallography; and, atmospheres, accompanied by discussions of circulation applicable as well as the gas giants.